Internalisasi Nilai-Nilai Islam Melalui Prophetic Parenting Di Panti Asuhan Kota Medan - Akmal Shah; Salminawati Salminawati; Zaini Dahlan (Jayapangus Press, 2025)
This study is grounded in the recognition that effective parenting should not only fulfill children’s physical and emotional needs but also instill religious values and moral virtues as the foundation of character formation. Prophetic parenting represents an educational concept inspired by the nurturing methods and exemplary character of the Prophet Muhammad (peace be upon him), emphasizing spiritual, emotional, and moral development through compassion, justice, and a humane approach. The purpose of this research is to explore the process of internalizing Islamic values through the implementation of prophetic parenting within orphanage settings, focusing on Darul Aitam Orphanage and Al Washliyah Ismailiyah Orphanage in Medan, Indonesia. This study employs a qualitative multi-site design to obtain an in-depth understanding of the phenomenon across different contexts. Data were collected through observation, in-depth interviews, and documentation, and analyzed descriptively using data reduction, data display, and conclusion-drawing techniques. The findings reveal that both orphanages implement prophetic parenting through caregivers’ exemplary conduct, support for children’s potential, fairness in fulfilling their needs, gradual educational guidance, and the reinforcement of religious observance. These practices foster children’s discipline in worship, learning motivation, empathy, and emotional stability. The study concludes that prophetic parenting contributes positively to the development of children’s character and spiritual growth, although challenges remain regarding resource limitations and the diversity of children’s backgrounds.